Tagging Named Entities in Croatian Tweets - Krešimir Baksa; Dino Golović; Goran Glavaš; Jan Šnajder (Slovenščina 2.0: Empirične, aplikativne in interdisciplinarne raziskave, 2016)
Named entity extraction tools designed for recognizing named entities in texts written in standard language (e.g., news stories or legal texts) have been shown to be inadequate for user-generated textual content (e.g., tweets, forum posts). In this work, we propose a supervised approach to named entity recognition and classification for Croatian tweets. We compare two sequence labelling models: a hidden Markov model (HMM) and conditional random fields (CRF). Our experiments reveal that CRF is the best model for the task, achieving a very good performance of over 87% micro-averaged F1 score. We analyse the contributions of different feature groups and influence of the training set size on the performance of the CRF model.